Utilizing Mobile Robots to Teach Dengue and Chikungunya Prevention in Brazilian Schools - Costa, R. B.; Gomes, Pedro H. L.; Silva, Luiz F. Rodriguez; Pastrana, M. A.; Gontijo, Maria C. C.; Luiz, M. S.; Muñoz, Daniel M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This paper introduces a novel approach to combating the spread of Dengue and Chikungunya, two prevalent arboviruses in tropical regions, especially in Brazil. The research presents a low-cost differential topology robot designed as an educational tool to raise awareness about mosquito breeding grounds among students and teachers in public schools across the Federal District, Brazil. Developed at the University of Brasilia, the robot is deployed in collaboration with the Federal District Health Department to support prevention campaigns in schools. The paper evaluates the effectiveness of this innovative tool in enhancing community engagement and improving health outcomes. The findings suggest that integrating robotics into health education can significantly elevate awareness and strengthen prevention strategies against arboviral diseases.